Enforceable Accounting Rules and Income Measurement by Early 20th Century Railroads - Sivakumar, Kumar; Waymire, Gregory (Journal of Accounting Research, 2003)
Abstract We investigate the extent to which income measurement by major early 20th‐century U.S. railroads shows evidence of lower income smoothness and increased conservatism following new fixed asset accounting rules issued by the Interstate Commerce Commission (ICC) in 1907 and 1908 and concurrent rate regulation regime shifts. Accounting rules promulgated by the ICC after the Hepburn Act of 1906 are the first accounting rules in U.S. history in which regulators could enforce such rules under federal law to increase compliance. Our samplewide results are more consistent with increased conservatism than with income smoothing. Additional tests indicate these effects are more pronounced for firms subject to more intense rate regulation by the ICC, which suggests that the tie‐in between accounting regulation and product/service market regulation influences how managers respond to new accounting rules.